THE BENEFITS OF ACTIVE COMPOUNDS IN KALANCHOE PINNATA (LMK) PERS ETHYL ACETATE FRACTION ON LUPUS ARTHRITIS MICE - Indriyanti, Niken; Soeroso, Joewono; Khotib, Junaidi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Ethyl acetate fraction of Kalanchoe pinnata (Lmk) Pers leaves (EF-KP) is a potential material to be developed for lupus treatment. The aim of this research was to measure the effects of the EF-KP on lupus arthritis mice. The research was performed by testing of CD123+IFN-α+ dendritic cells and CD68+IL-6+ macrophages as the main biomarkers by using flow cytometry methods, and then the outcomes were directly observed in the joint's tissue structure. The results of the research were analyzed by using statistics. The EF-KP reduces the relative percentages of CD123+IFN-α+ dendritic cells significantly (p<0.05) with the percentage of 32.95±8.25% (negative control); 23.28±9.31%* (EF-KP); 22.98±10.39%* (positive control). It also reduces the relative percentages of CD68+IL-6+ macrophages but not significantly (p>0.05). Finally, the outcome to the grade of joint damage was scored by using Pritzker method. The treated groups have one grade lower, and the joint spaces were narrower than the untreated group. The results show the ability of the active compounds in EF-KP, which are comparable to 0.042 mg/Kg quercetin, to inhibit the progress of lupus arthritis pathogenesis in mice. It reveals the effectiveness of the EF-KP in human with lupus arthritis. However, the further clinical research is necessary.